1992
DOI: 10.1515/znb-1992-1111
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosolate und verwandte Verbindungen, XII Nitrosolatokomplexe von Silber(I) / Nitrosolates and Related Compounds, XII Nitrosolato Complexes of Silver(I)

Abstract: X-ray analysis shows silver(I) aminomethylnitrosolate to have dimers as structural units, in which the W-shaped nitrosolate ions act as μ2-bridging ligands via the nitrogen atoms of the NO groups. The nearly planar dinuclear complexes form stacks, which are connected by additional AgO contacts leading to a kind of layer structure. These layers are held together by hydrogen bonds.Mononuclear complexes of composition [Ag(nitrosolate)L2] can be obtained from silver(I) ethylnitrosolate and bipyridyl in methanol an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The Ag(2)−Ag(2) distance is 3.157(4) Å, noticeably less than the 3.224(3)-Å Ag + −Ag + distance found in a similar structure in which some reduction of Ag + had occurred . It is just a little longer than the distances ranging from 2.655(2) to 3.058(1) Å that have been reported for Ag + −Ag + interactions in seven organic complexes of AgNO 3 . This indicates that a weak Ag + −Ag + interaction occurs in 12 of the 16 D6Rs per unit cell of this crystal. The Ag + ions at Ag(2) do not extend away from their D6Rs to avoid a Ag + −Ag + repulsion (see Figure ).…”
Section: Discussionmentioning
confidence: 72%
“…The Ag(2)−Ag(2) distance is 3.157(4) Å, noticeably less than the 3.224(3)-Å Ag + −Ag + distance found in a similar structure in which some reduction of Ag + had occurred . It is just a little longer than the distances ranging from 2.655(2) to 3.058(1) Å that have been reported for Ag + −Ag + interactions in seven organic complexes of AgNO 3 . This indicates that a weak Ag + −Ag + interaction occurs in 12 of the 16 D6Rs per unit cell of this crystal. The Ag + ions at Ag(2) do not extend away from their D6Rs to avoid a Ag + −Ag + repulsion (see Figure ).…”
Section: Discussionmentioning
confidence: 72%
“…Metal−Metal interactions are still ambiguous in polynuclear silver(I) compounds. In disilver(I) complexes containing an eight-membered Ag−N−C−N−Ag−N−C−N ring, silver−silver distances between 2.655 and 3.187 Å have been found, a few of these values being lower than twice the metallic silver radius (2.889 Å). Analogous rings are also known for Cu(I) ,, and Au(I)…”
Section: Introductionmentioning
confidence: 99%
“…As depicted in Figure , the DNM anion is planar like all NO-, NO 2 -, and CN-substituted methanide anions . In principle, three different planar structures of DNM are possible: (i) the anti/anti arrangement (as shown in Figure ), (ii) the syn/anti arrangement, and (iii) the syn/syn arrangement (Figure S4, Supporting Information) 3b. In agreement with the experiment, B3LYP/6-311+G(3df,2p) calculation revealed that the anti/anti form represents the most stable isomer followed by the syn/anti (+7.5 kcal/mol) and the syn/syn isomer (+13.1 kcal/mol).…”
mentioning
confidence: 97%
“…In a series of papers almost a century ago, Wieland described the synthesis of alkali and silver nitrosolates (M[RC(NO) 2 ], M = metal, R = organic substituent) . These nitrosolates can be obtained from unstable N , N ‘-dihydroxyamidines by disproportion in ammonia or by oxidation (KIO 4 ) in basic solution. For R = H, these procedures result in the formation of, e.g., potassium dinitrosomethanide when potassium hydroxide is used as a base. 1d,2b …”
mentioning
confidence: 99%
See 1 more Smart Citation